Analysis of the effect of concrete repair and self-healing due to corrosion using the impact-echo method - Aulia Chanief Rahita; Ahmad Zaki; Muhammad Fahri Al-Mizan; Sri Atmaja P. Rosyidi (Archives of Civil Engineering)
Reinforced concrete is a primary component in the construction industry and is susceptible to damage from corrosion, fires, and natural disasters. Steel corrosion in concrete has become a serious global issue, resulting in significant economic losses. Dealing with existing concrete damage requires considerable time and cost, making innovation in repair methods essential. One of the repair methods employed is grouting with cement grout and jacketing. Innovative solutions have emerged in self-healing concrete, allowing concrete to repair small cracks autonomously. One self-healing approach involves using bacteria to seal cracks in concrete. Identifying damage caused by corrosion in reinforced concrete is crucial for implementing appropriate protective measures. Non-Destructive Testing (NDT) methods offer a way to detect damage without compromising the physical structure. NDT methods have been used for evaluating and monitoring steel corrosion in reinforced concrete, including the Impact-Echo (IE) method. The most important result of this study was that the peak frequency values obtained from Impact Echo (IE) testing on concrete before and after corrosion showed a shift towards lower values, indicating a decrease in concrete quality due to corrosion. It was observed that after the repair process, there was an increase in peak frequency values detected with Impact Echo on each specimen, indicating the effectiveness of the repair method. These results are significant as they provide insight into the impact of corrosion on concrete quality, the effectiveness of repair methods, the correlation between concrete quality and structural strength, and the potential for non-destructive testing impact-echo methods to monitor concrete conditions.